IMPLEMENTASI SISTEM DETEKSI KUALITAS TELUR MENGGUNAKAN SENSOR LDR DAN LOADCELL - Irmawati Irmawati; T Husain; Fitriani Fitriani; Hasriani Hasriani; Ahyuna Ahyuna; Mochammad Agus Idris (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2026)
Abstract Eggs are one of the poultry products that serve as a source of high-quality animal protein, and contain various important nutrients such as essential amino acids, vitamins, and minerals. This commodity has significant economic value and a high level of consumption among the public due to its abundant availability, affordable price, and ease of distribution. In Indonesia, the types of eggs commonly consumed include broiler chicken eggs, free-range chicken eggs, duck eggs, and quail eggs. The process of sorting eggs based on quality is generally still done manually, such as by shining a light on the eggs. This method has limitations in terms of efficiency, consistency, and accuracy of assessment. This study aims to develop an automatic egg sorting system based on an Arduino Uno microcontroller, equipped with a LoadCell sensor for weight measurement and an LDR (Light Dependent Resistor) sensor to detect the intensity of light that penetrates the egg shell. The method used is an experimental method, by conducting a series of tests on egg samples to evaluate the system's performance as a whole. The experimental results show that the system can sort eggs automatically with a higher level of accuracy and efficiency than the manual method. In conclusion, this system can be an alternative applicable solution to improve the quality of the egg sorting process in the livestock and distribution industry.